2011
DOI: 10.1007/s10620-011-1973-7
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Viral Load (VLVL) Relapse Following Treatment of Naïve Patients with Chronic Hepatitis C

Abstract: VLVL relapse patients should be sought, because SVR to re-treatment is common despite genotype 1 cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The study of Hoefs et al also observes the same. 23 An immunomodulatory response against HCV may be due to the interferon induction and may therefore sustainably lower viral load (as observed in the present study). Higher "ALT levels" can sometimes suggest relapse before the reappearance of HCV RNA, but this parameter is not sufficiently reliable.…”
Section: Discussionsupporting
confidence: 59%
“…The study of Hoefs et al also observes the same. 23 An immunomodulatory response against HCV may be due to the interferon induction and may therefore sustainably lower viral load (as observed in the present study). Higher "ALT levels" can sometimes suggest relapse before the reappearance of HCV RNA, but this parameter is not sufficiently reliable.…”
Section: Discussionsupporting
confidence: 59%
“…In 10 (21.3%) relapsed patients, viral load remained within one log of the baseline value. Hoefs et al () also observed a very low viral load relapse in a proportion of naive patients, all of whom achieved sustained virologic response upon retreatment. In the present study, the viral load at relapse was below 2 log of the baseline value.…”
Section: Discussionmentioning
confidence: 90%
“…Despite these differences in study design, the frequency of VLVL was often similar. For example, in two studies including persons with a relapse after HCV treatment, a VLVL ≤1,000 IU/ml occurred in 4% [29], and a VLVL <5,000 IU/ml in 16% of persons [15]. In evaluations of blood samples of mostly treatment-experienced persons, a VLVL <600 IU/ml occurred in 2% [1], and a VLVL <1,000 in 3.5% of persons [29].…”
Section: Discussionmentioning
confidence: 99%
“…Viral loads <600 IU/ml [1] and <5,000 IU/ml [15] have been referred to as "very low viral loads" (VLVL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation